Effectiveness of Role Playing Cards (RPC) Learning Models Based on Madura Ethnic Entrepreneurship Values In Increasing Entrepreneurship Interest In Junior High School Students - Fajar Wahyudi Utomo Fajar; Shinta Dewi; Mariasih Mariasih; Masrin Masrin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This research aims to measure the effectiveness of the RPC (RPC) learning model based on Madurese entrepreneurial values in increasing junior high school students' interest in entrepreneurship. Method: The method used in this research is quantitative with a quasi-experimental design, a non-equivalent design (pretest and post-test), and a control group design. Results: The research results show that the RPC learning model based on Madurese ethnic entrepreneurial values effectively increases junior high school students' interest in entrepreneurship. This can be seen from the average percentage of N-gain in the experimental class is 60.70%. Meanwhile, the average percentage of N-Gain for the control class is 16.00%. So, the conventional learning model in the control class is ineffective in increasing interest in entrepreneurship among junior high school students. Novelty: This learning model is the only role-play learning model developed with a combination of card games and based on ethnic entrepreneurial values to increase students' interest in entrepreneurship. The effectiveness of this learning model can contribute to social studies learning; that is, through creative learning, students' entrepreneurial interest in entrepreneurial activities can increase.